Electrodeposition of Cu onto Au(111) from Deep Eutectic Solvents: Molar Ratio of Salt and Hydrogen Bond Donor. Issue 7 (27th January 2022) - Geng, Tanja; Zeller, Sven J.; Kibler, Ludwig A.; Ceblin, Maximilian U.; Jacob, Timo
Abstract: The electrodeposition of copper onto Au(111) from Deep Eutectic Solvents (DESs) type III has been studied by cyclic voltammetry. Investigations were carried out with mixtures of choline chloride (ChCl) and ethylene glycol (EG) or trifluoroacetamide (TFA). The eutectic compositions and temperatures were determined by differential scanning calorimetry (DSC). For the ChCl/EG DES, a eutectic ratio of 16 : 84 (ChCl:EG) was found instead of the previously reported ratio of 33 : 67. The electrodeposition of copper was studied for electrolytes with different ratios of ChCl to hydrogen bond donor (HBD) to resolve the influence of the composition on the deposition behavior. Both CuCl and CuCl2 were used as Cu salts. Underpotential deposition (UPD) is followed by bulk deposition with the diffusion rate of Cu species being dependent on the ratio of ChCl to HBD. With CuCl2, both Cu + and Cu 2+ species are reduced and deposited, whereby the two‐electron reduction is more dominant with higher chloride content and presence of EG. However, the properties of the Cu electrodeposition do not result from the freezing‐point depression of the DESs, but from the high concentration of ions. Abstract : Diving into Deep Eutectic Solvents : Having identified the eutectic ratio and temperature of two Deep Eutectic Solvents (DESs) type III, Cu electrodeposition on Au(111) from those DESs in different molar ratios was studied. The deposition mechanism is explained by the high ion concentration rather than the thermal properties of DESs. With more Cl − present and depending on the hydrogen bond donor, the diffusion rate of Cu species changes, and not only Cu + but also Cu 2+ is reduced.